Analysis of an integrated thermal separation and flashing cooling cogeneration cycle. (25th May 2021) - Shankar, R.; Rivera, W.
Highlights: Integration of thermal separation and flashing are made. The concept of flashing is introduced to boost the refrigerant in a cooling cogeneration plant. The electricity cost is reduced by three times compared with Kalina cycle system. The cooling output is improved by 35% compared to triple pressure cogeneration systems. Abstract: In this paper, a new combination of thermal separation and flashing cogeneration plant is proposed. This system could contribute to the development and enhancement of systems for the simultaneous production of power and cooling. The thermal separation and flashing process are included to utilize the energy supplied to the system more efficiently. In addition to the usual absorber condenser, generator, evaporator, and turbine components used in conventional cogeneration systems, a flashing chamber is introduced to increase the refrigerant production. By using the flashing chamber, the system performance is improved without increasing the heat supply to the system. The proposed system is suitable for all working mixtures usually utilized in absorption systems, but the ammonia-water mixture was considered for the present analysis. A rise in ammonia strong solution concentration results in a higher cogeneration output. At the hot fluid inlet temperature of 160 °C, the maximum outputs were 20.28 kW of power and 354.21 kW of cooling load. The overall energy utilization factor and exergy efficiencies are 0.47 and 43.87%, respectively.